The Study of the Density of Physical Space and the Hubble Constant (Global Journal of Science Frontier Research, 2020)
According to the description of physical space by general relativity and the principle of symmetry, this paper deduces the density property of physical space. On this basis, the author modified the metric tensor in Einstein's gravitational field equation, introduced the density factor of physical space into coordinate transformation, and deduced the gravitational field equation with a cosmological constant term. According to the equation, the cosmological constant term is the product of curvature and density factor of physical space, which is a negative increment of curvature, showing the property of repulsive force. This property could take the place of dark matter and dark energy. The author deduced the formula for calculating the Hubble redshift with space density term through Robertson-Walker metric and calculated the Hubble constant generated by space density according to the known material parameters of the universe. The calculated value is 74.6607Km•s -1 Mpc -1 , which is consistent with the observational results reported in the literature.
Keywords: space density; metric tensor; gravitational field equation; Hubble constant; Hubble redshift; Mossbauer spectrum